DIPG-16. DELAYED RT IN SELECT PATIENTS WITH DIPG. Issue 2 (22nd June 2018) - De Braganca, Kevin; Benitez, Viviana; Gilheeney, Stephen; Karajannis, Matthias; Khakoo, Yasmin; Kramer, Kim; Wolden, Suzanne
Abstract: INTRODUCTION: Patients with DIPG sometime present with mild symptoms and/or atypical MRI findings. Since palliative radiation therapy(RT) is the only effective treatment, a decision to treat with RT or wait for progressive symptoms and/or MRI changes arise. Progression free survival(PFS) and overall survival(OS) after delay in RT (>30 days from diagnosis) was compared against patients treated without delay. METHODS: An IRB retrospective waiver for patients with DIPG treated within Pediatrics at MSKCC from 2000–2016 was obtained. Univariate analysis of days to RT from diagnosis, gender, age, symptom duration, MRI (typical versus atypical) and association with PFS and OS via the Cox proportional hazard model was performed. Patients treated with radio-labeled antibody delivered via convection enhanced delivery were excluded (n=26). RESULTS: Thirty-nine patients with complete records were analyzed, median age: 6.8 years (range: 2–36.5), gender: 19 girls, atypical MRIs: 18. Six patients had delayed RT (days: 32, 33, 42, 74, 77 and 2793). The patient delayed 2793 days had a biopsy at progression demonstrating K27M staining. Patients had varying treatment courses: concomitant chemotherapy with RT, chemotherapy after RT and re-irradiation. Non-delayed versus delayed RT, PFS (6.7mo versus 10.4mo, p=0.184) and OS (12.7mo versus 12.9mo, p=0.485) were not associated with any significant difference. Univariate analysis found no associations. DISCUSSION: We found no association between delayed initiation of RT and PFS or OS in this retrospective analysis. Our data suggest that in a small subset of patients with DIPG presenting with atypical MRI findings and/or mild symptoms, it may be reasonable to delay initiation of RT.